Factors influencing tree biomass and carbon stock in the Western Himalayas, India - Kumar, Pardeep; Kumar, Abhishek; Patil, Meenu; Hussain, Sabir; Singh, Anand Narain (Frontiers in Forests and Global Change, 2024)
The assessment of tree biomass and its carbon (C) stock at the local and regional level is considered a crucial criterion for understanding the impact of changing environments on the global carbon cycle. In this context, we selected three sites in the western Himalayas, covering parts of Himachal Pradesh and north-eastern Haryana. Each study site experiences distinct climatic conditions, vegetation types, and elevations. We seek to elucidate the determinants of tree biomass and carbon stock across different forest types in the Western Himalayas. We found that temperate forests contributed the most biomass and carbon stock, with Cedrus deodara attaining the highest values of 782.6 ± 107.9 Mg/ha and 360 ± 49.7 Mg C/ha. In contrast, Quercus leucotrichophora mixed temperate had the lowest 286.6 ± 57.2 and 128.9 ± 25.7 Mg/C ha, respectively. Only a few species, such as Abies pindrow, Cedrus deodara, Quercus floribunda, and Quercus semecarpifolia, accounted for significant biomass and carbon stock. The lower elevation subtropical forests had the highest species richness (8–12 species) and stem density (558.3 ± 62.9 to 866.6 ± 57.7 trees/ha). Furthermore, tree diameter, total basal cover, and height emerged as the strongest predictors of biomass and C stock. The remaining variables showed no significant associations, including species diversity, climatic attributes and elevation. Thus, our study extended the assertion that vegetation composition and structural attributes, apart from climatic and topographic factors, are equally important in determining biomass and C stock in forest ecosystems. Our study indicated that the temperate forests in the western Himalayas possess significant carbon storage and climate change mitigation potential.